Estimating risk‐return relationships: An analysis of measures - Baucus, David A.; Golec, Joseph H.; Cooper, Juett R. (Strategic Management Journal, 1993)
Abstract We show that the risk‐return paradox can be partly explained by the choice of accounting risk and return measures. Returns computed with equity or assets from End‐of‐Period (EOP) annual reports produce negative risk‐return associations, while measures calculated using Beginning‐of‐Period (BOP) equity or assets yield more positive relationships. The likelihood of reporting negative relationships using EOP methods is accentuated by dividing samples at median returns. Below‐median firms suffer losses and may appear to have lower and more variable returns than above‐median firms, simply because of EOP methods. Our results show that mean and variance measures are unstable and risk‐return relationships vary inversely the number of firms reporting mean losses.